Dynamics of Parental Opioid Use and Children's Health and Well-Being: An Integrative Systems Mapping Approach - Smith, Jessica C.; Alderman, Leigh; Attell, Brandon K.; Avila Rodriguez, Wendy; Covington, Jana; Manteuffel, Brigitte; DiGirolamo, Ann M.; Snyder, Susan M.; Minyard, Karen (Frontiers in Psychology, 2021)
The seemingly intractable opioid epidemic compels researchers, the media, and families to better understand the causes and effects of this complex and evolving public health crisis. The effects of this crisis on people using opioids, maternal prenatal opioid exposure, and neonatal abstinence syndrome are well documented, but less is known about the impact of caregivers’ opioid use on children’s health and well-being. One challenge to understanding the effects of parental opioid use disorder (OUD) on child and adolescent outcomes is the numerous interrelated pathways in which a child’s health and well-being can be impacted. To better understand these dynamic relationships, we applied a systems mapping approach to visualize complex patterns and interactions between pathways and potential leverage points for interventions. Specifically, we developed a causal loop diagram system map to elucidate the complex and interconnected relationships between parental OUD, social determinants of health at the family and socio-environmental levels, family strengths, social supports, and possible adverse impacts on children’s physical and mental health and risks for future substance misuse. The goals of this research are to (1) identify factors and dynamics that contribute to the relationship between parental OUD and children’s health and well-being and (2) illustrate how systems mapping as a tool can aid in understanding the complex factors and dynamics of the system(s) that influence the well-being of children and their parents or primary caregivers.